Design and Analysis of Bow tie Multiband Cognitive Antenna Using Different Substrates - Bisht, V.; Khulbe, M. (Science and Technology - Recent Updates and Future Prospects Vol. 8, 2024)
Bowtie antennas give multifunction capability in modern wireless communication systems. The bow-tie antennas in this research work are used to design multiband antennas using different substrates. Bow tie designs are suitable for diverse multiband applications. We discuss design using dielectric substrates FR4, Arlon 217, Rogers and RT Duroid 6002.The antenna is designed at an operating frequency of 10GHz.With Arlon Cuclad 217 substrate multiband frequencies are 3.5GHz,7.0GHz,10.5 GHz, with FR4 substrate 11.2 GHz and with RTDuroid 6002 multibands are obtained at 1.8GHz,4.0GHz,6.0GHz 7.75GHz ,9.5GHz and 11.5 GHz and 13.5 GHz. Specific objectives of this research is comparative analysis of Bowtie Antenna by using various substrates and by changing operating frequency. The basic bowtie antenna is modified using a coplanar waveguide feed (CPW). The antenna behaviour is also studied as cognitive antenna by inserting an inductors of two different shapes zigzag and rectangular shapes between the bows of the antenna. With both the inductors inserted between the bow antenna all parameters obtained are same but radiation pattern and polar plots are different. The antenna operating frequency also switched from 10 GHz to 25GHz with the rectangular shape inductor. Thus, using a simple inductor gives frequency switching from 10 GHz to 25 GHz and with a switch in gain. Moreover, the inductor shape makes frequency switch of multibands 9.3 - 10.30 GHz to 11.35 GHz with also a gain switch from 4.99 to 6.9 GHz. Thus, these antennas makes them suitable to increase network links.